Dust particle charging in sheath - Gavrysh, G.O.; Kravchenko, O.Yu.; Lisitchenko, T.E. (Вопросы атомной науки и техники, 2014)
The charging and the screening of spherical dust particles in sheaths near the wall were studied using computer simulation. The three-dimensional PIC/MCC method and molecular dynamics method were applied to describe plasma particles motion and interaction with macroscopic dust grain. Calculations were carried out at different neutral gas pressures and wall potentials. Values of the charge of the dust particles and spatial distributions of plasma parameters are obtained by modelling. The results have shown that the charge of the dust particles in the sheath, as well as the spatial distribution of the ions and electrons near the dust particles, depend strongly on the wall potential. It is shown that for large negative values of the wall potential the negative charge of a dust particle decreases due to the decline of the electron density in its vicinity. In addition, the flow of energy of the ions on the surface of dust particles is increased due to better focusing effect of the dust particle field on ions. Зарядка и экранирование сферических пылевых частиц в приэлектродных слоях вблизи стенки были изучены с помощью компьютерного моделирования. Трехмерный PIC/MCC-метод и метод молекулярной динамики были применены для описания движения частиц плазмы и взаимодействия их с макроскопической пылинкой. Расчеты проводились при различных значениях давления нейтрального газа и потенциала стенки. Значения заряда пылевых частиц и пространственные распределения параметров плазмы получены при помощи моделирования. Результаты показали, что заряд пылевых частиц в приэлектродном слое, а также пространственные распределения ионов и электронов вблизи пылевых частиц сильно зависят от потенциала стенки. Показано, что при больших значениях потенциала стенки отрицательный заряд пылевой частицы уменьшается в связи с уменьшением плотности электронов в ее окрестности. Кроме того, поток энергии ионов на поверхность пылевой частицы увеличивается за счет лучшего фокусирующего действия поля пылевых частиц на ионы. Зарядка і екранування сферичних пилових частинок у приелектродних шарах поблизу стінки були вивчені за допомогою комп'ютерного моделювання. Тривимірний PIC/MCC-метод і метод молекулярної динаміки були застосовані для опису руху частинок плазми та взаємодії їх з макроскопічною пилинкою. Розрахунки проводились при різних значеннях тиску нейтрального газу і потенціалу стінки. Значення заряду пилових частинок і просторові розподіли параметрів плазми отримані за допомогою моделювання. Результати показали, що заряд пилових частинок у приелектродному шарі, а також просторові розподіли іонів і електронів поблизу пилових частинок сильно залежать від потенціалу стінки. Показано, що при великих значеннях потенціалу стінки негативний заряд пилової частинки зменшується в зв'язку зі зменшенням концентрації електронів поблизу неї. Крім того, потік енергії іонів на поверхню пилової частинки збільшується за рахунок кращої фокусуючої дії поля пилових частинок на іони.